2013
DOI: 10.3755/galaxea.15.201
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the shallow water holothurians in Camotes Islands, Central, Philippines

Abstract: Species diversity of holothurians in CamotesIslands, Cebu Philippines were studied as baseline data for resource and ecological management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Field sampling was done following the method of Tanduyan et al (2013). A transect-quadrat method was used where an 80-meter transect was laid down perpendicular to the coast and was replicated thrice in a 5-meter interval starting from the shoreline.…”
Section: Sea Cucumber Eld Samplingmentioning
confidence: 99%
“…Field sampling was done following the method of Tanduyan et al (2013). A transect-quadrat method was used where an 80-meter transect was laid down perpendicular to the coast and was replicated thrice in a 5-meter interval starting from the shoreline.…”
Section: Sea Cucumber Eld Samplingmentioning
confidence: 99%
“…revealed that the number of sea cucumbers found was likely to be higher if the sampling was held at night (Personal communication; (Wisesa et al, 2018). It was stated by (Tanduyan et al, 2013) that H. scabra had a frequency found twice as much at night compared to daytime.…”
Section: Densitymentioning
confidence: 99%